Love and dance as transformative powers. Issue 8 (14th September 2019) - McGowan, Margaret M.
ABSTRACT: This essay attempts to show how thinking about dance furthers our understanding of Renaissance love. It explores visions of dancing at court, manifestations both of innocent pleasure and of the desire to provoke love. An important focus is the dance – la volta  – which brought male and female dancers into close physical proximity allowing the poet who recreates its lively movement to transmit feelings of desire, of transport and transformation such that dance seems to stand for love. While Latin and French poets – Dorat, Jamyn and Desportes – provide evidence of choreographic and amorous performance, the love sonnets and other poems of Pierre de Ronsard are studied in detail to show how dance and love are integrated into poetic rhythms which capture and extend the range of their transformative power.